Respiratory Measures of Musical Theater Singers, Classical Singers, and Non-singers - Burnette, Payton; Cox, Kathleen T.; Rangarathnam, Balaji (My University, 2015)
This study looked for respiratory trends between musical theater singers, classical singers, and a non-singer control group using the KayPentax Phonatory Aerodynamic System. Results of Kruskal-Wallis and graphical comparison analysis indicated that the groups differed on several measures including maximum phonation time and peak expiratory airflow. Conclusions and recommendations for future research are discussed.
Keywords: Singers; Respiration; Musical theater; Phonatory Aerodynamic System